Analisis Pengaruh Geometri Jalan Tambang Dari Front Penambangan ke Stockpile Terhadap Keselamatan Kerja PT Caritas Energi Indonesia Sarolangun Jambi - Rika Fitriani; Guskarnali Guskarnali; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2020)
PT Caritas Energi Indonesia (CEI) is a company engaged in coal mining in Sarolangun Jambi. Based on the work accident data in the last 5 years of PT Caritas Energi Indonesia on the hauling coal getting road using dump truck transport Equipment Scania 380 P that resulted casualty and inflicted loss for the company both in terms of equipment repair and treatment of victims. The method on this research is to use quantitative data to calculate the width of straight road for sixty one segments, the width of bend road for fourteen segments, calculating the superelevation for fourteen segments, calculating hauling road slope (grade) for sixty one segments, calculating the cross slope for sixty one segments, analyzing the effect of road geometry on Occupational Health and Safety. The width of the straight road is 7 m for one line and 11 m for two lines, all segments were qualified, except Segment 0+400, Segment 0+700, Segment 1+600, thereforeit is necessary to increase the width of road to fit the standard, the width of the bend roadis 8 m for a single line and 13 m for two lines, all segments were qualified, exceptSegment 0+500, Segment 1+000 and Segment 4+100, superelevationbased on standard is 4%, not all of the superelevations were qualified so it needs to increase the width of the bend road so that it might avoid the centrifugal force while passing through the bend, all the grade of segmentswere qualified. PT Caritas Energi Indonesia didn’t have cross slope so the company needs to pay attention and make cross slope according to the standard of 40 mm/m. The geometry of the mining road of PT Caritas Energi Indonesia weren’t qualified, it might effectedwork accident so that it needs improvement accordance with standards